2011
DOI: 10.5012/bkcs.2011.32.8.2988
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fluorescent Shape Memory Polyurethanes Grafted with Various Dyes

Abstract: Shape memory polyurethane (SMPU), grafted with a fluorescent dye (Rhodamine, Mehylene violet, or Fluorescein) through an allophanate linking, was tested for the fluorescence and the shape recovery effect. The main chain of SMPU was composed of 4,4'-methylenebis(phenylisocyanate) (MDI), poly(tetramethyleneglycol) (PTMG), and 1,4-butanediol (BD), and a fluorescent dye was connected through a second MDI linked to the carbamate moiety of the main chain. Three series of SMPU, differing according to their dye conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Luminescent polymers have potential applications in safety marking systems, organic light‐emitting diodes, and luminescence converters for ultraviolet (UV)‐emitting diodes. In the present investigation, PU was grafted with PL dyes that were not tested previously by the authors . Then, a non‐woven PL‐PU fibre was prepared using the electrospinning method.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Luminescent polymers have potential applications in safety marking systems, organic light‐emitting diodes, and luminescence converters for ultraviolet (UV)‐emitting diodes. In the present investigation, PU was grafted with PL dyes that were not tested previously by the authors . Then, a non‐woven PL‐PU fibre was prepared using the electrospinning method.…”
Section: Introductionmentioning
confidence: 92%
“…For example, a PU derivative that sustains shape recovery at −30 °C and an electrolytically responsive PU derivative that functions in water have been reported . Recently, the present authors have reported a PU series grafted with characteristic fluorescent dyes that exhibit unobstructed fluorescence together with high tensile strength . Similarly to the above‐mentioned grafted functional polymers, other characteristic fluorophores [aminofluorene (A), naphthalimide (NI), naphtholbenzein (NB), and phenosafranin (P)] need to be tested as promising functional molecules to graft onto PU chains, and the resultant photoluminescent (PL) PU derivatives can be used to prepare a non‐woven nanofibre using the electrospinning method.…”
Section: Introductionmentioning
confidence: 99%
“…This PU surface grafting method has been reported in the literature [18][19][20][21][22] and was previously demonstrated by our group in developing functionalized PUs; for example, PUs that exhibited flexibility at low temperatures [23], electric attraction in aqueous solutions [24], pH sensitivity [25], and photoluminescence [26] were successfully developed. Specifically, 2-hydroxyethyl methacrylate (HEMA), a vinyl group with a hydroxyl end, was attached to the PU side using MDI as a grafting agent.…”
Section: Introductionmentioning
confidence: 93%
“…The C=O stretching peaks at approximately 1700 and 1729 cm -1 were used to analyze the intermolecular interactions, such as hydrogen bonding and dipole-dipole interactions, between the hard segments. The bonded carbonyl band (1700 cm -1 ) appeared at a lower wavenumber than did the free carbonyl group band (1729 cm -1 ) [25,26]. The relative intensities of the bonded and free carbonyl stretching vibrations were used to compare the degree of phase separation (DPS) among the different series of polymers, which indicated the change in the molecular interactions between the hard segments.…”
Section: Ir and Thermal Analysismentioning
confidence: 99%
“…In this study, we grafted calcein markers using different polymerized procedures to investigate their fluorescent-loading effectiveness. Since previous studies have indicated that calcein-grafted materials could have long-lasting fluorescence, 19,20 we tried to explore the long-term fluorescent imaging of PU polymers using the copolymerization method. Physiochemical and fluorescent properties of calcein-loaded PU scaffolds have been evaluated and analyzed by different methods.…”
Section: Introductionmentioning
confidence: 99%